Entrepreneurship in the Region - Fritsch, Michael; Schmude, Jürgen (International Studies in Entrepreneurship, 2006)
Entrepreneurship in the Region approaches many different aspects of entrepreneurship from a regional perspective. The regional influences on entrepreneurship analyzed entail regional peculiarities and disparities in new business formation processes, the success and the employment effects of new firms, the importance of social capital and of network structures as well as entrepreneurship education and training provided in the regions. The articles in this book provide strong evidence for the importance of regional factors that shape entrepreneurship and new firm formation processes. It is shown that regional differences of start-up rates and entrepreneurial attitudes are not at all elusive but tend to be rather persistent and prevail over longer periods of time. The evidence clearly suggests that the regional level can be an appropriate starting point for entrepreneurship policy and that research on the issue may considerably benefit from properly accounting for the spatial dimension.